Preclinical Evaluation of Baicalin for the Treatment of Diabetic Nephropathy: A Systematic Review and Meta-Analysis - An, Hengtong; Liu, Luyao; He, Tongtong; Chen, Xiaohan; Jin, Xiaofei; Zhou, Xiaohong; Gao, Weijuan (Planta Medica, 2025)
Scutellaria baicalensis, a widely used medicinal herb in traditional Chinese medicine, is frequently employed in the treatment of diabetic nephropathy (DN). Its primary active constituent, baicalin, has shown significant therapeutic potential in animal models of DN; however, no comprehensive and systematic evaluation of its therapeutic effects and underlying mechanisms in DN has yet been conducted. This meta-analysis aimed to assess the efficacy of baicalin in DN treatment and elucidate its pharmacological mechanisms. Relevant studies were retrieved from databases including Web of Science, PubMed, Embase, CNKI, Wanfang Data, and VPCS, covering the literature up to November 2024. Study quality was evaluated using SYRCLEʼs risk of bias tool, and statistical analyses were performed with STATA 12. Primary outcomes included blood urea nitrogen (BUN), serum creatinine (SCR), and fasting blood glucose (FBG), while secondary outcomes encompassed urinary protein (UP), triglycerides (TG), total cholesterol (TC), inflammatory markers, fibrosis indicators, and oxidative stress parameters. Subgroup analyses, publication bias assessments, and sensitivity analyses were conducted to ensure result reliability. A total of 14 studies involving 221 rodents met the inclusion criteria. Baicalin significantly reduced BUN, SCR, FBG, TG, TC, UP, interleukin-6 (IL-6), interleukin-1 beta (IL-1β), tumor necrosis factor-alpha (TNF-α), malondialdehyde (MDA), and fibronectin (FN) levels while enhancing superoxide dismutase (SOD) activity. These findings suggest that baicalin improves kidney function, reduces proteinuria, corrects lipid metabolism, and alleviates inflammation, oxidative stress, and fibrosis. This meta-analysis concludes that baicalin exhibits significant therapeutic potential in DN models, acting via anti-inflammatory, antioxidant, and antifibrotic mechanisms.
Keywords: Scutellaria baicalensis; Lamiaceae; baicalin; diabetic nephropathy; animal model; systematic review; mechanisms of action; meta-analysis